Effects of White Potato Preparation on Subjective Appetite, Food Intake and Glycemic Response in Healthy Older Adults (P08-083-19) - Lee, Jennifer (Curr Dev Nutr, 2019)
OBJECTIVES: Although some epidemiological studies have linked potato consumption to obesity, diabetes, and mortality, there are limited studies on the effects of potatoes on appetite, food intake, and glycemic regulation in older adults. Therefore, the objective was to compare the effects of white potato preparation on subjective appetite, short-term food intake, and glycemic response in healthy older adults (>65 y). METHODS: Using a within-subject, repeated-measures design, 20 participants (age: 70.5 ± 0.7 y; BMI: 24.2 ± 0.6 kg/m(2)) completed five treatment conditions. Following an overnight fast, participants completed five treatment conditions (∼283 kcal) of baked potatoes, mashed potatoes, fried French fries, white bread, or continued to fast. Treatment meals were matched for available carbohydrates (33.1 g) and total fat (13.7 g). Subjective appetite and glycemic response were measured at baseline and over 120 min post-meal consumption using visual analogue scales and capillary blood samples, respectively. An ad libitum pizza lunch was provided to measure food intake at 120 min. RESULTS: Change from baseline subjective appetite and subjective appetite incremental area under the curve (iAUC) were lower after all treatment meals compared with meal skipping (P < 0.01). Ad libitum pizza lunch food intake was lower after all treatment meals compared with meal skipping by 175–215 kcal (P < 0.02). However, cumulative food intake (treatment meal + ad libitum food intake) did not differ among test conditions (P = 0.26). Change from baseline blood glucose and blood glucose iAUC were higher after all treatment meals compared with meal skipping (P < 0.001), but did not differ from each other. CONCLUSIONS: White potatoes suppressed subjective appetite and short-term food intake compared with meal skipping, suggesting that white potatoes do not bypass regulatory control mechanisms of energy intake in healthy older adults. FUNDING SOURCES: Alliance for Potato Research & Education.